Capsule Endoscopy: What We Know and What Is New in the Horizon - Chauhan, Virender; Tanwar, Amit; Nijhawan, Sandeep (Journal of Digestive Endoscopy, 2019)
Capsule endoscopy (CE) is an advancing noninvasive technology primarily meant for small-bowel visualization, which has expanded its scope and has become a game changer in evaluation and management of various gastrointestinal (GI) diseases with special emphasis on obscure GI bleeding. The aim of this review is to know the basic aspects of CE and recent advances with clinical evidence.
Keywords: capsule endoscopy; celiac disease; Crohn's disease; obscure gastrointestinal bleed; small bowel